ANALISIS KONSEP LIVING AL-QUR'AN DAN HADITS DALAM KEHIDUPAN MASYARAKAT - Rusdiah, Rusdiah (Al-Manba, 2025)
Living Al-Qur'an and Hadith is an approach in Islamic studies that emphasizes understanding how the teachings of the Qur'an and Hadith are actualized in the daily lives of Muslims. This approach was born from the awareness that the holy text does not only stop at the level of theory or reading, but also becomes a practical guide that is manifested through the behavior, traditions, and culture of society. Living Al-Qur'an and Hadith examines how Muslims collectively or individually interpret, practice, and bring to life the values contained in the Qur'an and Hadith, both in the form of religious rituals, social customs, and daily activities. This approach is relevant because it provides a real picture of the interaction between the holy text and the dynamics of social life in various cultural, geographical, and era contexts. Thus, Living Al-Qur'an and Hadith not only examines the normative aspects of the text, but also reveals the diversity of meanings and implementations of Islamic teachings that develop in the lives of Muslim communities. However, the implementation of lifelong education still faces various challenges, such as gaps in access, lack of public awareness, and limited support from various parties. Therefore, collaboration between the government, educational institutions, and the community is needed to realize inclusive and sustainable education.